Selective separation and recovery of selenium from copper anode slime by compound leaching followed by sulfate roasting. (August 2022) - Zeng, Yanliang; Zou, Jianbo; Liao, Chunfa; Liu, Fupeng; Zhou, Xun
Highlights: Selective separation and recovery of Se from copper anode slime can be achieved. Se was effectively enriched by approximately 200% after first compound leaching. More than 99.39 % of Se was separated by using sulfate roasting, whereas the extraction of the remaining metals in were all less than 0.5 %. The evaporative separation process of Seis controlled by intraparticle Diffusion Control. Abstract: In this research, selenium was selectively separated and recovered from copper anode slime by a hydrometallurgical-pyrometallurgy union process. In the first compound leaching process with H2 SO4, HCl and NaCl media, the pre-removal of As, Sb, and Bi was achieved, and the removal efficiencies were 85 %, 83 %, and 91 %, respectively. Selenium was effectively enriched by approximately 200 % after first compound leaching. Sulfate roasting method was used to selectively separate selenium in the second stage. In this study, more than 99.39 % of selenium was separated with concentrated sulfuric acid amount to first leaching residues ratio (H2 SO4 / first compound leaching residues ratio) of 0.30 mL/g at 500 °C for 25 min, which enabled selenium to be selectively separated from the other elements. The kinetics of sulfation roasting of Se-enriched residues show that the selective separation of selenium conforms to the Avrami multiphase liquid–solid region reaction, the activation energy of the reaction is 28.118 kJ/mol, and the reaction efficiencies equation is k = 3.607e -3382/T, indicating that it is internal diffusion-controlled.